Radiation Dose Reduction in Digital Plain Radiography of the Knee after Total Knee Arthroplasty - Kloth, J. K.; Tanner, M.; Stiller, W.; Burkholder, I.; Kauczor, H. U.; Ewerbeck, V.; Weber, M. A. (RöFo - Fortschritte auf dem Gebiet der Röntgenstrahlen und der bildgebenden Verfahren, 2015)
Purpose: To reduce radiation exposure of frequently performed radiographs of the knee in follow-up of total-knee arthroplasty ensuring accurate assessment by using objective quality control criteria.Materials and Methods: In this prospective randomized study 278 radiographs of the knee in follow-up of total-knee arthroplasty were performed with standard and 37 % reduced radiation dose. The evaluation of the plain-radiographs was conducted using the following criteria: bone-implant interface, implant-surface character, implant-implant discrimination and periarticular heterotopic ossification. Two radiologists evaluated these criteria using a score ranging from 1 (definitely assessable) to 4 (not assessable). If a single criterion had been evaluated with a score ≥ 3 or more than 2 criteria with ≥ 2 points, the radiograph was score das „not assessable“. The study was designed as non-inferiority-trial.Results: 100 % of examined radiographs were scored as assessable, hence no statistical inferiority between the examinations with standard and reduced dose could be observed. Singular assessment of the defined criteria was likewise dose-independent.Conclusion: Plain-radiography of the knee following total-knee arthroplasty can be performed with 63 % of standard dose without loss of diagnostic validity.Key points:• Due to the non-inferiority of digital radiographs of the knee joint after total-knee arthroplasty done with 37 % reduced image receiver dose we recommend the tested speed class of SC 800 as a new reference value for digital radiographs with this indication.Citation Format:• Kloth JK, Tanner M, Stiller W et al. Radiation Dose Reduction in Digital Plain Radiography of the Knee after Total Knee Arthroplasty. Fortschr Röntgenstr 2015; 187: 685 – 690
Keywords: skeletal-appendicular; digital radiography; radiation safety